Qualidade da informação contábil-financeira: estudo sobre as observações relacionadas às demonstrações contábeis contidas nos relatórios de auditoria das principais empresas concessionárias brasileiras de água e esgoto - Forgi, Renato de (2017)
The research described in this work had as main objective to make a qualitative and quantitative analysis of the independent audit reports of the Mixed Economy Societies working in the water and sewage segment with State control in the years of 2012 to 2015. The methodology is exploratory, quantitative and Qualitative, through the technique of content analysis based on the accounting information published in the official journal, sent to the CVM - Comissão de Valores Mobiliários or available on the website. The result of this research allowed to identify the main notes of 20 companies of the sample, in the period of 2012 to 2015, resulting in 171 notes. It was observed that 8 demonstrations presented a critical quality level, representing 11.2% of the total analyzed and that 23 statements presented qualified opinions, and there may also be an indication of impairment of the accounting quality of these statements, corresponding to 32% of the analyzed statements. It was also observed that 40 accounting statements (56.3%) did not present any qualifications, and could indicate a satisfactory level of accounting compliance of the statements of this segment